2021
DOI: 10.1021/acs.biomac.1c01264
|View full text |Cite
|
Sign up to set email alerts
|

Carbosilane Glycodendrimers for Anticancer Drug Delivery: Synthetic Route, Characterization, and Biological Effect of Glycodendrimer–Doxorubicin Complexes

Abstract: The complexity of drug delivery mechanisms calls for the development of new transport system designs. Here, we report a robust synthetic procedure toward stable glycodendrimer (glyco-DDM) series bearing glucose, galactose, and oligo(ethylene glycol)-modified galactose peripheral units. In vitro cytotoxicity assays showed exceptional biocompatibility of the glyco-DDMs. To demonstrate applicability in drug delivery, the anticancer agent doxorubicin (DOX) was encapsulated in the glyco-DDM structure. The anticance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 90 publications
(134 reference statements)
1
16
0
Order By: Relevance
“…However, we always observed particles around 10 nm, representing a dominant fraction corresponding to small clusters containing from several units to high tens of DDM molecules, depending on the generation. The formation of small clusters was also previously reported for other carbosilane glycodendrimers …”
Section: Resultssupporting
confidence: 82%
“…However, we always observed particles around 10 nm, representing a dominant fraction corresponding to small clusters containing from several units to high tens of DDM molecules, depending on the generation. The formation of small clusters was also previously reported for other carbosilane glycodendrimers …”
Section: Resultssupporting
confidence: 82%
“…This indicated that the flexibility of the skeleton and the availability of its hydrophobic interior, as well as the formation of larger assemblies in buffer solution, are key factors for the interaction. In subsequent research, the same authors determined the cytotoxicity toward breast and ovarian cancer cell lines and noncancer BJ cell line (human fibroblast cell type) of several dendrimers bearing glucose, galactose, or oligo(ethyleneglycol)‐modified galactose peripheral units and prepared glycodendrimer–doxorubicin complexes (Figure 5; Mullerova et al, 2022). The results obtained indicated that these systems are suitable candidates for the encapsulation and subsequent release of doxorubicin, which is more efficiently released in acidic environments (tumor conditions) than under physiological conditions (pH 7.4).…”
Section: Pharmaceutical Applications Of Carbosilane Dendritic Moleculesmentioning
confidence: 99%
“…Example of CBS glycodendrimer as drug carrier in antitumor therapy. Reprinted with permission from Mullerova et al (2022). Copyright 2022, American Chemical Society…”
Section: Pharmaceutical Applications Of Carbosilane Dendritic Moleculesmentioning
confidence: 99%
“…In most cases, the excess reagent is readily separable by using extraction or evaporation. Only in the case of compound-L1-9-bearing dimethylammonium groups, the separation requires organic solvent nanofiltration (OSN) [35][36][37]-an effective method which we previously exploited for the purification of CS-dendrimers [27,28,38,39]. The key feature of synthetic amphiphiles, essential for their investigation in biological environments, is their water-solubility.…”
Section: Synthesis and Characterization Of Carbosilane Amphiphilic De...mentioning
confidence: 99%
“…Our long-term interest has been focused on CS dendrimers with a well-defined structure that express multivalent presentation of functional moieties at their periphery [27][28][29][30][31] and, due to the incompatibility of their hydrophobic interior with polar periphery, can be considered as unimolecular micelles [32]. Here we turn our attention to a development of new versatile synthetic protocols for amphiphilic building blocks capable of self-assembly to regular micelles and other supramolecular objects.…”
Section: Introductionmentioning
confidence: 99%